2022
DOI: 10.3390/plants11121542
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Gradients Shaping the Freshwater Bryophyte Communities of Croatia (Western Balkans)

Abstract: A comprehensive field survey of 527 sites on 293 watercourses across Croatia revealed 76 sites (14.42%) in which bryophytes were the dominant part of the macrophyte vegetation. Using classification and ordination analyses, we obtained five community types segregated across the gradients of several climatic, physiographic and water chemistry parameters. The Didymodon tophaceus–Apopellia endiviifolia and the Berula erecta-Cratoneuron filicinum communities were mostly confined to the clean and basic karstic river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These rivers flow over carbonate bedrock which influences water pH and alkalinity, as well as species assemblages where basophilous, i.e., acid-sensitive, taxa dominate. An important influence of geology, water pH and alkalinity on aquatic bryophytes has been already demonstrated on the European level [1,2,4,5,30,39,57] and beyond [6,17,40,59], and clear segregation of aquatic bryophytes along the alkalinity and pH gradient was recently demonstrated for Croatian bryophytedominated watercourses as well [22]. The latter study identified three communities characterized by different basophilous species which were mostly associated with karstic rivers of the Dinaric Ecoregion, and two communities in small rivers situated in the Pannonian Ecoregion, which were dominated by a high share of hygrophyte taxa inhabiting periodically flooded river margins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These rivers flow over carbonate bedrock which influences water pH and alkalinity, as well as species assemblages where basophilous, i.e., acid-sensitive, taxa dominate. An important influence of geology, water pH and alkalinity on aquatic bryophytes has been already demonstrated on the European level [1,2,4,5,30,39,57] and beyond [6,17,40,59], and clear segregation of aquatic bryophytes along the alkalinity and pH gradient was recently demonstrated for Croatian bryophytedominated watercourses as well [22]. The latter study identified three communities characterized by different basophilous species which were mostly associated with karstic rivers of the Dinaric Ecoregion, and two communities in small rivers situated in the Pannonian Ecoregion, which were dominated by a high share of hygrophyte taxa inhabiting periodically flooded river margins.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the species included in our study preferred near-neutral to basic water, with the mosses Eucladium verticillatum, Didymodon tophaceues, Palustriella falcata, Brachythecium rivulare, Fissidens crassipes and Cinclidotus aquaticus, as well as the liverworts Apopellia endiviifolia and Chiloscyphus polyanthos, being most strongly associated with higher water pH and having high frequencies and abundance in the watercourses of the Dinaric Ecoregion. This ecoregion is known to harbor greater diversity regarding freshwater bryophytes [15] and their communities [22] since its fast, cold montane and semi-montane karstic rivers with larger and more stable substrates provide more suitable habitats than the lowland rivers of the Pannonian Ecoregion, which are usually slow and warmer, with dominantly sandy and gravelly substrates. This was demonstrated in our study as well, with the highest number of species recorded in montane and mid-altitude small watercourses, followed by montane and mid-altitude medium and large watercourses of the Continental Subecoregion, which are both characterized by the dominance of large and medium substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, mosses are distributed vertically, and the plant coverage and species diversity at the bottom of the slope are high (table 1). Under the dominance of the subtropical monsoon climate, the region has abundant rainfall, and the high and steep slopes are washed by unidirectional runoff, which reshapes the distribution of mosses [29]. High and steep rocky slopes are difficult to retain water, so air humidity, as an important source of water for mosses, plays an important role in the development of mosses.…”
Section: Discussionmentioning
confidence: 99%